Korelasi Nilai Indeks Prestasi Kumulatif dengan Jumlah Hafalan Juz 30 Mahasiswa Program Studi Pendidikan Agama Islam STAIN Majene: Studi Kasus: Data Mahasiswa Aktif Prodi PAI angkatan 2017 Jurusan Tarbiyah dan Keguruan STAIN Majene - Darwis; Muhammad Idris (PRODI PENDIDIKAN AGAMA ISLAM (PAI) SEKOLAH TINGGI AGAMA ISLAM NEGERI MAJENE, 2021)
Abstract The purpose of the research that will be studied is to describe the close correlation between the Grade Point Average and the total memorization of juz 30 students of the Islamic Religious Education Study Program (PAI) STAIN Majene. The method used in this study to collect data is by means of direct interviews with students who will be used as research samples. Analysis of the data used to describe the close correlation between the two variables is using Pearson correlation analysis. The results obtained in this study that the close correlation between the grade point average and the number of memorizations juz 30 of students of PAI STAIN Majene obtained a positive correlation. So, the higher the GPA value, the higher the memorization of Juz 30 students while the correlation coefficient value was 0.187, which means the relationship between the two the variable is very weak, it means that the academic achievement value does not have much contribution with the large number of juz memorization obtained by the 2017 PAI study program students. Keywords: Description of correlation, Grade Point Average